Fenomena ‘Entertainment Architecture’ di Indonesia dan Perkembangan dalam Arsitektur (EMARA: Indonesian Journal of Architecture, 2016)
The entertainment architecture phenomenon that started in many developed countries in the second half of the 20th century has marked the birth of architectural designs whose primary purpose is to provide interactive entertainment for their users. This literature study aims to analyze a similar phenomenon that grows as an archetype of architectural designs, particularly in Indonesia. The method used in this study is a qualitative research method with a naturalistic paradigm. This study aims to investigate and find the meaning of "entertainment architecture," specific characteristics in visual and architectural forms, and how these characteristics can be read as a type in the development of architecture. The study results conclude that the phenomenon of "entertainment architecture" in Indonesia can be read as the development of new ideas in thinking and making architecture through the figure, its looks, and its form, which are different from the language of pre-existing buildings.